An Introduction to Decentralized Finance (DeFi) - Johannes Rude Jensen; Victor von Wachter; Omri Ross (Complex Systems Informatics and Modeling Quarterly)
Decentralized financial applications (DeFi) are a new breed of consumer-facing financial applications composed as smart contracts, deployed on permissionless blockchain technologies. In this article, we situate the DeFi concept in the theoretical context of permissionless blockchain technology and provide a taxonomical overview of agents, incentives and risks. We examine the key market categories and use-cases for DeFi applications today and identify four key risk groups for potential stakeholders contemplating the advantages of decentralized financial applications. We contribute novel insights into a rapidly emerging field, with far-reaching implications for the financial services.